Forgetting the Line: Taoist Methods in Contemporary Ink Painting - Hsu, Peter (Auckland University of Technology, 2024)
This practice-led research project uses Taoist methods and contemporary ink painting to explore the intersection of spontaneous creativity and embodied knowledge. Taoist martial arts and meditation are practices that emphasise exploration and understanding of spontaneous creativity, or wuwei, also known as ‘action through non-action’. These practices utilise the Chinese concepts of ting-chin and tso-wang, or ‘listening energy’ and ‘sitting-forgetting’, as ways to access and act from this state of spontaneous creativity. By applying Taoist meditation and sensing techniques to an ink-based calligraphic painting practice, I investigate how the action of painting can arise from a state of wuwei. I argue that this state allows creation to proceed in an intuitive, organic manner based in embodied knowledge. I explore how the fluidity of ink and brush, when used in a painting employing Taoist methods, creates work that reflects the immediacy of ever-changing moment and how those moments continually layer on themselves to create the present. This exploration will address my key questions: how is spontaneity understood and used as a source of creativity and how can I use Taoist methods to explore spontaneous creativity through painting?